Negative rhetoric in the user generated content of Nigerian news media (2016)
Despite its enhancement of citizens’ freedom of expression and participation through content creation, studies have shown that the digital space enabled by Web 2.0 technologies is not without some negative consequences such as prevalence of negative rhetoric with serious implications for social cohesion. However, the veracity of this claim, as related to the Nigerian context, needs further empirical investigation. Guided by Face Negotiation Theory, this study, therefore, through quantitative content analysis and textual analysis, examined the nature of issues articulated by readers in the comment sections of purposively selected Nigerian news media- Premium Times, The Punch, Sahara Reporters, and The Vanguard. Analyses of 3, 796 users’ comments show that User-Generated Content (UGC) in the comment sections of the selected news media have more incidences of negative rhetoric (n=2,023; 53.3%) than positive (n=1,298; 34.2%) and neutral (n=475; 12.5%) comments. Besides, while negotiating self-worth and personas (face), users employ textual codes that carry elements of impoliteness, harassment, abuse, hatred, threats, incitement, and danger, and are capable of promoting cultural contradictions, ethnic dichotomies, and socio-political dissonance among Nigerians. A discourse culture where citizens predominantly employ negative rhetoric to negotiate conflicts is inimical to social and structural cohesion of the nation.